Diseño de una campaña comunicacional para promover la inserción al sistema educativo en las mujeres del barrio Las Cuatro Esquinas del cantón Pujilí en el período académico marzo- agosto 2014 - Valencia Jama, Tamara Crystina (2015)
The research objective is to promote the integration of women in the education system, identifying patterns and factors to have influence that women don’t integrate in the educative system in “Las 4 esquinas” neighborhood- Pujilí. Through the analysis and conceptual frameworks are evidence that there are still relegated as women, preventing them from participating in education. However, women have begun to raise awareness of the importance of education and their participation in it. Through the use of methodology, valuable information are obtained around this problem that involves all of society, this is what we intended, is not staying on statistics rather interpret reality and generate criticism and proposals. Through an exhaustive analysis and established proposal to design a communicational campaign to promote the culture of participation and inclusion in education women, and on equal terms as men, calling for the whole society contribution and generate awareness of equality that humans possess.